PEMBUATAN BAHAN AJAR BERBASIS ICT DENGAN MENGINTEGRASIKAN MSTBK MATERI GETARAN, ENERGI DAN MOMENTUM UNTUK MENCAPAI KOMPETENSI SISWA KELAS XI SMA - Widya Fibrianti (PILLAR OF PHYSICS EDUCATION, 2014)
Good human resources can be produced by emphasizing graduate with good character who have skills and relevant knowledge. The fact in learning physics in school, Physics has not been fully linked to  other disciplines. One solution in this case is to create learning materials with integrating Math, Sciences, technology, disasters, and good character based on ICT. The purpose of this research is to determine the  validity, description, practicality, and effectivity of learning material with integrating relevant knowledge and skills based on ICT. The type of this research is research and development (R&D) with before-after    experiment design. As an object of this research is learning material with integrating MSTBK based on ICT. The instruments that used to collect data are validity sheet, practicality sheet, learning outcomes test sheet, and observation sheet for the character. There are two results of the data analysis. First, learning material with integrating relevant knowledge and skills based on ICT for the first semester of grade XI is valid with average of 83,42 by experts and 76,82 by practitioners. Learning material’s design consists of home, identity materials, introduction, learning materials, exercises, evaluation, reference, download, chat, and discussion forums. Second, learning materials is practic with an average value is 88,24. This learning materials is effective to increase student learning outcomes and improve the students’s character value